Provider Perspectives on Fertility and Fertility Preservation Discussions Among Women With Cystic Fibrosis - Jessica Corcoran PhD, CRNP, CPNP-PC; Caitlin Campbell PhD, RN; Sigrid Ladores PhD, RN, PNP, CNE, FAAN (SAGE Publishing, 2023)
Cystic Fibrosis (CF) is a genetic disorder that primarily impacts the respiratory and gastrointestinal systems. With advances in treatment and medications, the life expectancy of people with CF is continuing to increase with current life expectancy at 47 years of age. Given the increased life expectancy, people with CF are interested in childbearing but may have CF specific fertility issues that should be addressed by their CF healthcare provider. Currently, these conversations are not occurring or are suboptimal. This study aimed to investigate the practices of cystic fibrosis (CF) healthcare providers regarding fertility and fertility preservation (FP) discussions among women with CF. This was a qualitative, descriptive study. Twenty CF healthcare providers were interviewed including nurses, nurse practitioners, social workers, and dieticians among other disciplines. The semi-structured interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Four themes emerged from the provider interviews about their fertility and FP discussion practices: (1) Change over Time; (2) CF Team Provides Primary Care including Reproductive Health Care; (3) Patient Support and Advocacy; and (4) Barriers and Facilitators to FP Discussions. The results of this study demonstrate an opportunity for CF healthcare providers to deliver patient-centered care. However, CF providers need to be educated on fertility and FP options. Additionally, there is a need for a more standardized structure of care to address the reproductive health of women with CF. The findings from this study may also be useful to non-CF providers who deliver care to women whose chronic illnesses impact their reproductive health.